High-polarization antiferroelectric ceramic material, capacitor and preparation method of high-polarization antiferroelectric ceramic material

By solidly dissolving the antiferroelectric materials of two different crystal phases to form a quasi-homomorphic boundary structure of relaxed ferroelectric bodies, the problem of poor performance and stability of existing antiferroelectric materials when improving spontaneous polarization is solved, and the improvement of high polarization and stable performance is achieved.

CN119638409AActive Publication Date: 2025-03-18KUNSHAN QINGYUAN ELECTRONIC TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411741591.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

When existing antiferroelectric materials improve spontaneous polarization, their performance and stability are poor, making it difficult to meet the needs of high-performance electronic devices.

Method used

By solid-solution of antiferroelectric materials with two different crystal phases with molar ratios of (1-x):x, a quasi-homomorphic phase boundary structure of relaxed ferroelectric bodies is formed, and the solid-solution ratio is precisely controlled to improve polarization and dielectric properties.

Benefits of technology

It significantly improves the polarization and dielectric properties of the material, and at the same time improves the stability performance, suitable for applications in high temperature and high stress environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638409A_ABST
    Figure CN119638409A_ABST
Patent Text Reader

Abstract

The invention provides a high-polarization antiferroelectric ceramic material, a capacitor and a preparation method of the high-polarization antiferroelectric ceramic material, the high-polarization antiferroelectric ceramic material is formed by solid solution of two antiferroelectric materials with different crystal phases, the molar ratio of the antiferroelectric materials is (1-x): x, x is 0.02-0.20, and the high-polarization antiferroelectric ceramic material has a relaxor ferroelectric quasi-homomorphic phase boundary structure. According to the anti-ferroelectric ceramic material provided by the invention, the solid solution proportion of ferroelectric materials with different crystal phases is accurately controlled, and a quasi-homomorphic phase boundary structure of the relaxor ferroelectric is ingeniously introduced, so that the polarization performance and the dielectric performance of the material are remarkably improved, and the comprehensive improvement of the stability performance of the material is also realized. The high-polarization anti-ferroelectric ceramic capacitor provided by the invention has extremely high energy storage density due to the unique anti-ferroelectric property, the anti-ferroelectric ceramic capacitor has excellent power density, stored energy can be quickly released in a short time, the anti-ferroelectric ceramic capacitor can keep stable performance in a relatively wide temperature range, and the high-polarization anti-ferroelectric ceramic capacitor can be widely applied to the field of high-power electronic devices. And the system can work reliably under various environmental conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic materials, in particular to a high-polarization antiferroelectric ceramic material, a capacitor and a preparation method thereof. Background Art

[0002] Antiferroelectric materials have attracted much attention in the fields of electronic devices, capacitors, sensors, storage devices, etc. due to their unique electrical properties and application potential. These materials can exhibit polarization behavior similar to ferroelectric materials under the action of an external electric field, but they present a special non-polarized state, namely the antiferroelectric phase, under zero electric field. This property gives antiferroelectric materials unique advantages in certain applications, such as higher stability and lower power consumption.

[0003] However, the types of antiferroelectric materials currently available are relatively limited, mainly including traditional typical antiferroelectric materials such as PbZrO3 (lead zirconate), PbHfO3 (lead hafniumate) and AgNbO3 (silver niobate). The spontaneous polarization of these materials is usually low, generally around 40uC cm -2 About. In some applications, higher spontaneous polarization is required to achieve better performance, but existing materials often sacrifice antiferroelectric stability while improving polarization, which limits their application in high-performance electronic devices. For example, Pb(Zr,Ti)O3 (lead zirconate titanate) is a typical antiferroelectric material. By adjusting the ratio of Zr and Ti, the polarization properties of the material can be adjusted to a certain extent. However, when trying to increase the polarization by increasing the Ti content, the antiferroelectric stability of the material is affected, resulting in reduced reliability in some applications.

[0004] It should be noted that the above introduction to the technical background is only for the convenience of providing a clear and complete description of the technical solutions of the present application and for the convenience of understanding by those skilled in the art. It cannot be considered that the above technical solutions are well known to those skilled in the art simply because they are described in the background technology section of the present application.

[0005] In view of the above, there is an urgent need to provide a high-polarization antiferroelectric ceramic material, a capacitor and a preparation method thereof to solve the above problems. Summary of the invention

[0006] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a high-polarization antiferroelectric ceramic material, a capacitor and a preparation method thereof, so as to solve the problem of poor performance and stability of antiferroelectric materials in the prior art when improving spontaneous polarization.

[0007] To achieve the above-mentioned purpose and other related purposes, the present invention provides a high-polarization antiferroelectric ceramic material, which is formed by solid solution of two antiferroelectric materials with different crystal phases in a molar ratio of (1-x):x, wherein x=0.02~0.20, and the high-polarization antiferroelectric ceramic material has a quasi-isomorphic phase boundary structure of a relaxor ferroelectric.

[0008] Optionally, the two antiferroelectric materials of different crystal phases are selected from any one of PbZrO3, PbHfO3, AgNbO3 and NaNbO3.

[0009] Optionally, the general chemical formula of the high polarization antiferroelectric ceramic material is: (1-x)PbZrO3-xPbHfO3, or (1-x)PbZrO3-xAgNbO3, or (1-x)AgNbO3-xNaNbO3.

[0010] Optionally, x=0.025~0.100.

[0011] The present invention provides a method for preparing a high-polarization antiferroelectric ceramic material, the method for preparing the high-polarization antiferroelectric ceramic material comprising:

[0012] S1: weighing oxides and / or carbonates according to a stoichiometric ratio, mixing and then grinding for the first time to obtain a first powder;

[0013] S2: performing a first heat treatment on the first powder;

[0014] S3: grinding the first powder for a second time to obtain a second powder;

[0015] S4: bonding and pressing the second powder to obtain a ceramic material of a preset shape;

[0016] S5: performing a second heat treatment on the ceramic material to obtain a high-polarization antiferroelectric ceramic material.

[0017] Optionally, in step S1: the oxides include lead oxide, zirconium oxide, hafnium oxide and niobium oxide, and the carbonates include silver carbonate and sodium carbonate.

[0018] Optionally, in step S1: if a high polarization antiferroelectric ceramic material with a general chemical formula of (1-x)PbZrO3-xPbHfO3 is prepared, lead oxide, zirconium oxide and hafnium oxide are weighed; if a high polarization antiferroelectric ceramic material with a general chemical formula of (1-x)PbZrO3-xAgNbO3 is prepared, lead oxide, zirconium oxide, silver carbonate and niobium oxide are weighed; if a high polarization antiferroelectric ceramic material with a general chemical formula of (1-x)AgNbO3 is prepared, silver carbonate, sodium carbonate and niobium oxide are weighed.

[0019] Optionally, the first grinding and the second grinding are both performed by ball milling.

[0020] Optionally, in step S2: the first heat treatment is a calcination treatment, the calcination treatment temperature ranges from 800°C to 950°C, and the calcination treatment time ranges from 2h to 4h.

[0021] Optionally, the first powder needs to be pressed before the first heat treatment in step S2.

[0022] Optionally, in step S4, the specific steps of bonding and pressing the second powder are as follows: adding a binder to the second powder for granulation to form a flowing powder, taking an appropriate amount of the flowing powder for tableting and pressing to obtain a ceramic material of a preset shape.

[0023] Optionally, in step S5: the second heat treatment is a sintering treatment, the sintering treatment temperature range is 1100° C. to 1250° C., and the sintering treatment time range is 2 h to 4 h.

[0024] The present invention also provides a high polarization antiferroelectric ceramic capacitor, which comprises a ceramic dielectric layer and metal layers on the upper and lower surfaces of the ceramic dielectric layer. The ceramic dielectric layer is any one of the antiferroelectric ceramic materials described above.

[0025] The present invention also provides a method for preparing a high polarization antiferroelectric ceramic capacitor, the method for preparing a high polarization antiferroelectric ceramic capacitor comprising: a method for preparing a high polarization antiferroelectric ceramic material as described in any one of the above and

[0026] S6: coating metal on the upper and lower surfaces of the high polarization antiferroelectric ceramic material to form a metal layer;

[0027] S7: Perform a third heat treatment to form a high polarization antiferroelectric ceramic capacitor.

[0028] Optionally, in step S7: the third heat treatment is a sintering treatment, the sintering treatment temperature ranges from 750°C to 850°C, and the sintering treatment time ranges from 15min to 60min.

[0029] Optionally, in step S7: the third heat treatment is performed in a nitrogen atmosphere.

[0030] As described above, the high polarization antiferroelectric ceramic material, capacitor and preparation method thereof of the present invention have the following beneficial effects:

[0031] The high-polarization antiferroelectric ceramic material and the preparation method thereof proposed in the present invention, by precisely controlling the solid solution ratio of ferroelectric materials of different crystalline phase phases, ingeniously introduces the quasi-isomorphic phase boundary structure of the relaxor ferroelectric, which not only significantly improves the polarization performance and dielectric properties of the material, but also achieves a comprehensive improvement in its stability performance, opening up a new path for the research and application of antiferroelectric materials; the high-polarization antiferroelectric ceramic capacitor and the preparation method thereof proposed in the present invention have extremely high energy storage density due to their unique antiferroelectric properties. Under the action of an electric field, antiferroelectric ceramics can undergo a phase transition between an antiferroelectric state and a ferroelectric state, and this process is accompanied by a large amount of energy conversion, so that the capacitor can store and release more energy. The antiferroelectric ceramic capacitor has an excellent power density and can quickly release the stored energy in a short time. The antiferroelectric ceramic capacitor can maintain stable performance within a wide temperature range, which enables them to work reliably under various environmental conditions. The antiferroelectric ceramic capacitor is expected to play an important role in more fields and promote the progress and development of related technologies. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 Shown is a polarization change curve of the high polarization antiferroelectric ceramic material of the present invention.

[0033] Figure 2 Shown is a graph of the frequency dependence of the dielectric constant and loss of the high polarization antiferroelectric ceramic material of the present invention.

[0034] Figure 3 Shown is a curve diagram of dielectric constant variation of the high polarization antiferroelectric ceramic material of the present invention.

[0035] Figure 4 Shown is a flow chart of the method for preparing the high polarization antiferroelectric ceramic material of the present invention.

[0036] Figure 5 Shown is a flow chart of a method for preparing a high polarization antiferroelectric ceramic capacitor of the present invention. DETAILED DESCRIPTION

[0037] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0038] When describing the embodiments of the present invention in detail, for the sake of convenience, the cross-sectional views showing the device structures will not be partially enlarged according to the general scale, and the schematic views are only examples, which should not limit the scope of protection of the present invention.

[0039] For ease of description, spatial relational terms such as "under", "below", "below", "below", "above", "on", etc. may be used herein to describe the relationship of one structure or feature shown in the drawings to other structures or features. It will be understood that these spatial relational terms are intended to include other directions of the device in use or operation in addition to the directions depicted in the drawings. In addition, when a layer is referred to as being "between" two layers, it can be the only layer between the two layers, or there may be one or more intervening layers. As used herein, "between..." means including the end point values.

[0040] In the context of the present application, a structure in which a first feature is described as being "above" a second feature may include embodiments in which the first and second features are formed in direct contact, and may also include embodiments in which additional features are formed between the first and second features, such that the first and second features may not be in direct contact.

[0041] See also Figures 1 to 5 It should be noted that the illustrations provided in this embodiment are only used to illustrate the basic concept of the present invention in a schematic manner, and the illustrations only show components related to the present invention rather than being drawn according to the number, shape and size of components in actual implementation. In actual implementation, the type, quantity and proportion of each component may be changed arbitrarily, and the component layout may also be more complicated.

[0042] Embodiment 1

[0043] The present embodiment provides a high-polarization antiferroelectric ceramic material, which is formed by solid solution of two antiferroelectric materials of different crystal phases in a molar ratio of (1-x):x, wherein x=0.02-0.20, including 0.02 and 0.20, for example, x=0.025, 0.050, 0.075, 0.10, 0.125, 0.150, 0.175, 0.20, and the high-polarization antiferroelectric ceramic material has a quasi-morphological phase boundary (Morphotropic Phase Boundary, MPB) structure of a relaxor ferroelectric, that is, antiferroelectric phases and ferroelectric phases with different symmetries exist simultaneously in the MPB system structure.

[0044] The coexistence of the antiferroelectric phase and the ferroelectric phase greatly promotes the flipping process between the antiferroelectric and ferroelectric phases, so that under the action of an external electric field, the antiferroelectric phase can quickly and efficiently transform into the ferroelectric phase, thereby releasing a huge polarization charge. Compared with single-phase antiferroelectric materials, this composite structure significantly improves the polarization strength of the material.

[0045] The presence of the MPB structure makes the material exhibit more complex dielectric behavior near the phase boundary, including an increase in the dielectric constant, a decrease in dielectric loss, and an acceleration of the dielectric response. These excellent dielectric properties are not only conducive to improving the signal transmission efficiency of electronic devices, but also can achieve higher energy conversion efficiency in energy storage devices. In addition, by adjusting the x value, the dielectric properties of the material can be further fine-tuned to meet the specific needs of different application scenarios.

[0046] Traditional antiferroelectric materials are prone to performance degradation under temperature changes or mechanical stress, which limits their application in extreme environments. High-polarization antiferroelectric ceramic materials form a more stable crystal structure by solid-dissolving two antiferroelectric materials with different crystal phases. This structural stability not only improves the thermal stability of the material, enabling it to maintain stable electrical properties over a wide temperature range; it also enhances the mechanical strength of the material and reduces cracks or breakage caused by external forces. Therefore, this material has broad application prospects in high-temperature and high-stress environments such as aerospace and automotive electronics.

[0047] In a specific example that can be implemented, the two antiferroelectric materials of different crystal phases are selected from any one of PbZrO3, PbHfO3, AgNbO3 and NaNbO3. Specifically, the chemical formula of the high polarization antiferroelectric ceramic material is: (1-x) PbZrO3-xPbHfO3, or (1-x) PbZrO3-xAgNbO3, or (1-x) AgNbO3-xNaNbO3.

[0048] like Figures 1 to 3 As shown, taking the (1-x)PbZrO3-xPbHfO3 system as an example, when deeply studying the system, a series of different x values ​​were selected within the set x numerical range. Through precise experimental design and rigorous testing methods, the polarization properties and dielectric properties of the system were comprehensively and systematically analyzed. The specific test results are as follows:

[0049] In order to compare the high polarization antiferroelectric ceramic material of the present application with the traditional single-phase antiferroelectric ceramic material, the value of x is selected to be 0-0.10, specifically 0, 0.025, 0.050, 0.075, and 0.100.

[0050] Figure 1 The polarization change curve is shown in Figure 1.5 MV cm -1 In the electric field environment, the polarization of the (1-x)PbZrO3-xPbHfO3 system changes when x is different. When x is in the range of 0 to 0.10, the polarization performance of the system shows a trend of increasing first and then decreasing as the x value increases. When x = 0.075, the polarization intensity of the system reaches the maximum value of 75uC cm -2It can be seen that the quasi-isomorphic phase boundary is at x = 0.075, the interaction between the antiferroelectric phase and the ferroelectric phase in the system is the strongest, and the phase transition process is the most rapid and efficient.

[0051] Figure 2 The frequency dependence of dielectric constant and loss is shown in the figure. The upper curve group in the figure shows the change of dielectric constant at different frequencies. It can be seen that the dielectric constant also shows a trend of increasing first and then decreasing with the change of x value. At x = 0.075, that is, the dielectric constant reaches a peak near the quasi-isomorphic phase boundary; the lower curve group in the figure shows the change of energy loss at different frequencies. It can be seen that the energy loss shows a trend of decreasing first and then increasing with the change of x value. At x = 0.075, that is, the energy loss value is the smallest near the quasi-isomorphic phase boundary. This shows that at this x value, the system has better charge storage capacity and lower energy loss.

[0052] Further, Figure 3 The dielectric constant variation curve shows that under the environment of 10kHz, with the increase of x value, the dielectric constant of the system shows a trend of first increasing and then decreasing. At x=0.075, that is, near the quasi-isomorphic phase boundary, the dielectric constant reaches a peak value.

[0053] From the above, it can be seen that when x = 0.075, the (1-x)PbZrO3-xPbHfO3 system has the best polarization performance, charge storage capacity and lower energy loss. Preferably, x = 0.025 to 0.100. In the range of x = 0 to 0.20, the polarization performance of the system shows a trend of first increasing and then decreasing, the dielectric constant also shows a trend of first increasing and then decreasing, and the energy loss shows a trend of first decreasing and then increasing. Because the changes in their trends are more obvious in the range of 0 to 0.10, the figure of this embodiment is not shown in the range of x = 0.10 to 0.20.

[0054] Embodiment 2

[0055] like Figure 4 As shown, this embodiment provides a method for preparing a high-polarization antiferroelectric ceramic material, which is prepared by a solid phase method. The method for preparing a high-polarization antiferroelectric ceramic material includes the following steps:

[0056] S1: weighing oxide and / or carbonate powders according to a stoichiometric ratio, mixing and then grinding for the first time to obtain a first powder;

[0057] S2: performing a first heat treatment on the first powder;

[0058] S3: grinding the first powder for a second time to obtain a second powder;

[0059] S4: bonding and pressing the second powder to obtain a ceramic material of a preset shape;

[0060] S5: performing a second heat treatment on the ceramic material to obtain a high polarization antiferroelectric ceramic material.

[0061] The specific steps of the preparation method of high polarization antiferroelectric ceramic material are as follows:

[0062] Step S1: obtain oxides and / or carbonates, the oxides include lead oxide, zirconium oxide, hafnium oxide and niobium oxide, the carbonates include silver carbonate and sodium carbonate, and are divided into wide-mouth bottles; place the above raw materials in an oven for baking to obtain dry oxides and carbonates, and the purity is higher than 98%; wherein the baking temperature is 100°C to 150°C, and the baking time is more than 10 hours; the wide-mouth bottle mouth is sealed with weighing paper during the baking process, the purpose of baking is to dry the materials and improve their purity, and the actual baking temperature and baking time can also be set according to actual needs. According to the stoichiometric ratio in the chemical formula of the high-polarization antiferroelectric ceramic material, weigh the required oxides and carbonates respectively. It should be noted here that the preparation of antiferroelectric materials usually requires the use of oxides containing the required elements. Although carbonates are not the main raw materials directly used to prepare antiferroelectric materials, in some cases where they are needed, carbonates may be used as auxiliary raw materials or precursors to participate in the preparation process. In this embodiment, the corresponding oxides or oxides and carbonates can be obtained as needed to prepare antiferroelectric materials.

[0063] For example, if (1-x)PbZrO3-xPbHfO3 is prepared, lead oxide, zirconium oxide and hafnium oxide are weighed separately; if (1-x)PbZrO3-xAgNbO3 is prepared, lead oxide, zirconium oxide, silver carbonate and niobium oxide are weighed separately; if (1-x)AgNbO3-xNaNbO3 is prepared, silver carbonate, sodium carbonate and niobium oxide are weighed separately.

[0064] Specifically, the first grinding method is ball milling, the weighed oxide and carbonate are mixed and added to a ball mill for the first grinding, during the grinding process, the material in the ball mill is directly ball milled with a ball mill, the ball milling speed and ball milling time can be set according to actual needs, and no specific restrictions are made here, or, anhydrous ethanol is used as a ball milling medium, the material, ball mill, the specific gravity of anhydrous ethanol, the ball milling speed and ball milling time can be set according to actual needs, and no specific restrictions are made here, so as to obtain the first powder. It should be noted here that when using a ball milling medium, the mixed slurry after ball milling needs to be dried to remove the ethanol in the mixed slurry, and the baking temperature and drying time can be set according to actual needs, and no specific restrictions are made here.

[0065] Preferably, the first powder is passed through a sieve with a preset mesh size to refine the powder, so that the powder is fully mixed and evenly mixed, the contact surface area is increased, and the reaction activity or mixing efficiency is improved.

[0066] Step S2: performing a first heat treatment on the first powder. Before the first heat treatment, the first powder can be pressed into blocks to facilitate placing the block-shaped first powder into a muffle furnace for the first heat treatment. In a specific example that can be implemented, the first heat treatment is a calcination treatment, and the calcination treatment temperature range is 800°C to 950°C, and the calcination treatment time range is 2h to 4h. The specific calcination treatment temperature and calcination treatment time can be set according to actual needs and are not limited here.

[0067] Step S3: Place the blocky first powder in a grinding body for grinding, and then place it in a ball mill for a second grinding to obtain a second powder. The second grinding method can also be a ball milling method. The specific ball milling method is the same as the first grinding method, which will not be described here. It should be noted that the second grinding is finer than the first grinding, so as to facilitate the subsequent acquisition of ceramic materials.

[0068] Step S4: Bond and compress the second powder, that is, granulate and compress the second powder. Specifically, add a binder to the second powder for granulation to obtain a flowing powder with good fluidity. The flowing powder needs to be ground and sieved so that the binder and the second powder are fully mixed. The flowing powder with good fluidity has good uniformity and fluidity. Among them, the binder is preferably polyvinyl alcohol (PVA). The mass fraction and amount of polyvinyl alcohol added, as well as the mesh size of the flowing powder can be set according to actual needs, and no specific restrictions are made here.

[0069] The powder with good fluidity is placed for more than 24 hours to obtain a fluid powder with stable performance; an appropriate amount of the fluid powder is put into a tablet press for tablet pressing to obtain a dense and uniform ceramic material. The tablet pressing pressure range and holding time, as well as the weight, shape and size of the ceramic material can be set according to actual needs. In this embodiment, the shape of the ceramic material is a disc. Furthermore, the ceramic material can be pressed twice to obtain a more dense and uniform ceramic material.

[0070] In this step, the ceramic material also needs to be debonded, the temperature is quickly raised in a short time, and the temperature is kept warm for a certain period of time. The debonding temperature and the heat preservation time can be set according to actual needs and are not specifically shown here. It is only necessary to remove the adhesive in the ceramic material.

[0071] Step S5: perform a second heat treatment on the ceramic material. The second heat treatment is a sintering treatment. The ceramic material is placed in a sintering furnace for sintering treatment. The sintering treatment temperature range is 1100℃~1250℃, and the calcination treatment time range is 2h~4h. The specific heating time, sintering treatment temperature and sintering treatment time can be set according to actual needs and are not limited here.

[0072] Three groups of ceramic material preparation experiments are conducted as follows:

[0073] Comparative example: PbZrO3

[0074] Obtain lead oxide and zirconium oxide and pack them in wide-mouth bottles, seal the mouth of the wide-mouth bottles, place the lead oxide and zirconium oxide in the wide-mouth bottles in an oven for baking, dry them, and obtain lead oxide and zirconium oxide with a purity higher than 98%. According to the stoichiometric ratio in the chemical formula of PbZrO3, weigh the required lead oxide and zirconium oxide respectively. Mix the weighed lead oxide and zirconium oxide and add them to a ball mill for the first ball milling to obtain the first powder. The first powder is calcined at 850°C and then ball milled for the second time to obtain the second powder. Polyvinyl alcohol is added to the second powder for granulation to obtain a flowing powder with good fluidity, and the flowing powder is ground and sieved. The powder with good fluidity is placed for more than 24 hours to obtain a flowing powder with stable performance. Take an appropriate amount of the flowing powder and put it into a tablet press for tablet pressing to obtain a dense and uniform disc-shaped ceramic material. The disc-shaped ceramic material was subjected to debinding treatment and sintering at 1200°C to obtain the antiferroelectric material PbZrO3. After testing, the dielectric constant of the obtained antiferroelectric material PbZrO3 was 230 and the maximum polarization was 57uC cm -2 .

[0075] Example 2-1: 0.95PbZrO3-0.05PbHfO3

[0076] Obtain lead oxide, zirconium oxide and hafnium oxide and pack them in wide-mouth bottles, seal the mouth of the wide-mouth bottles, place the lead oxide, zirconium oxide and hafnium oxide in the wide-mouth bottles in an oven for baking and drying, and obtain lead oxide, zirconium oxide and hafnium oxide with a purity higher than 98%. According to the stoichiometric ratio in the chemical formula of 0.95PbZrO3-0.05PbHfO3, weigh the required lead oxide, zirconium oxide and hafnium oxide respectively. Mix the weighed lead oxide, zirconium oxide and hafnium oxide and add them to a ball mill for the first ball milling to obtain the first powder. The first powder is calcined at 850°C and then ball milled for the second time to obtain the second powder. Polyvinyl alcohol is added to the second powder for granulation to obtain a flowing powder with good fluidity, and the flowing powder is ground and sieved. The powder with good fluidity is placed for more than 24 hours to obtain a fluid powder with stable performance. An appropriate amount of the fluid powder is put into a tablet press for tablet pressing to obtain a dense and uniform disc-shaped ceramic material. The disc-shaped ceramic material is subjected to a binder removal treatment and a 1200°C sintering treatment to obtain an antiferroelectric material 0.95PbZrO3-0.05PbHfO3. After testing, the dielectric constant of the obtained antiferroelectric material 0.95PbZrO3-0.05PbHfO3 is 245, and the maximum polarization is 62uC cm -2 .

[0077] Example 2-2: 0.95PbZrO3-0.05PbHfO3

[0078] Obtain lead oxide, zirconium oxide and hafnium oxide and pack them in wide-mouth bottles, seal the mouth of the wide-mouth bottles, place the lead oxide, zirconium oxide and hafnium oxide in the wide-mouth bottles in an oven for baking and drying, and obtain lead oxide, zirconium oxide and hafnium oxide with a purity higher than 98%. According to the stoichiometric ratio in the chemical formula of 0.95PbZrO3-0.05PbHfO3, weigh the required lead oxide, zirconium oxide and hafnium oxide respectively. Mix the weighed lead oxide, zirconium oxide and hafnium oxide and add them to a ball mill for the first ball milling to obtain the first powder. The first powder is calcined at 850°C and then ball milled for the second time to obtain the second powder. Polyvinyl alcohol is added to the second powder for granulation to obtain a flowing powder with good fluidity, and the flowing powder is ground and sieved. The powder with good fluidity is placed for more than 24 hours to obtain a fluid powder with stable performance. An appropriate amount of the fluid powder is put into a tablet press for tablet pressing to obtain a dense and uniform disc-shaped ceramic material. The disc-shaped ceramic material is subjected to a binder removal treatment and a sintering treatment at 1150°C to obtain an antiferroelectric material 0.95PbZrO3-0.05PbHfO3. After testing, the dielectric constant of the obtained antiferroelectric material 0.95PbZrO3-0.05PbHfO3 is 260 and the maximum polarization is 65uC cm -2 .

[0079] From the comparative experiments, it can be seen that the dielectric constant and polarization values ​​of the antiferroelectric ceramic material formed by the solid solution of two antiferroelectric materials with different crystal phases are improved compared with the single-phase antiferroelectric material.

[0080] The interaction between quasi-isomorphic phase boundaries and the interface effect promote the redistribution of charges and the diversification of polarization mechanisms, thereby significantly improving the dielectric constant of ceramic materials. Specifically, the charge accumulation at the quasi-isomorphic phase boundary, the increase in space charge limited current, and the possible dipole orientation effect act together on the composite system, allowing the ceramic material to store more charge under the action of the electric field, thereby exhibiting a higher dielectric constant. At the same time, the stress coupling between different crystal phases and the possible formation of microdomain structures. The lattice constant differences and strain states between different crystal phases induce the formation of microdomains, which can more easily undergo orientation changes under the action of the electric field, thereby contributing greater polarization strength. In addition, the charge accumulation at the quasi-isomorphic interface may also form an additional polarization mechanism, further improving the polarization value of the material.

[0081] Embodiment 3

[0082] The present embodiment provides a high polarization antiferroelectric ceramic capacitor, which includes a ceramic dielectric layer and a metal layer on the upper and lower surfaces of the ceramic dielectric layer, wherein the ceramic dielectric layer is an antiferroelectric ceramic material as described in any one of the first embodiments. The metal layer on the upper and lower surfaces of the ceramic dielectric layer is a metal electrode of the ceramic capacitor, and the metal electrode is any one of conductive metals such as silver (Ag), copper (Cu), aluminum (Al), palladium (Pd), and nickel (Ni) alloy. In the present embodiment, the metal layer is preferably a silver layer, which has good conductivity. The thickness and shape of the electrode layer can be set according to actual needs, and no specific restrictions are made here.

[0083] In a specific implementation example, the high polarization antiferroelectric ceramic capacitor further includes a plastic encapsulation layer to encapsulate the ceramic dielectric layer, exposing only the metal leads to prevent the ceramic dielectric layer from being damp or contaminated. The material of the plastic encapsulation layer can be a polymer material such as resin.

[0084] The high-polarization antiferroelectric ceramic capacitor proposed in this embodiment has an extremely high energy storage density due to its unique antiferroelectric properties. Under the action of an electric field, antiferroelectric ceramics can undergo a phase change between an antiferroelectric state and a ferroelectric state. This process is accompanied by a large amount of energy conversion, which enables the capacitor to store and release more energy. Antiferroelectric ceramic capacitors have excellent power density and can quickly release stored energy in a short period of time. Antiferroelectric ceramic capacitors can maintain stable performance over a wide temperature range, which enables them to work reliably under various environmental conditions. Antiferroelectric ceramic capacitors are expected to play an important role in more fields and promote the progress and development of related technologies.

[0085] Embodiment 4

[0086] like Figure 5 As shown, this embodiment provides a method for preparing a high-polarization antiferroelectric ceramic capacitor, and the method for preparing a high-polarization antiferroelectric ceramic capacitor includes the method for preparing an antiferroelectric ceramic material as described in any one of the second embodiments, and S6: coating metal on the upper and lower surfaces of the antiferroelectric ceramic material respectively to form a metal layer; S7: performing a third heat treatment to form a high-polarization antiferroelectric ceramic capacitor.

[0087] Furthermore, before coating the metal on the upper and lower surfaces of the ceramic material, the ceramic material is polished, cleaned and dried to obtain a clean ceramic material with a preset thickness.

[0088] In a specific implementation example, the third heat treatment is a sintering treatment, the sintering treatment temperature range is 750°C to 850°C, the sintering treatment time range is 15min to 60min, and the specific heating rate, sintering treatment temperature and sintering treatment time can be set according to actual needs, and are not limited again. Further, the sintering treatment is carried out in a nitrogen atmosphere.

[0089] In a specific implementation example, the method of coating the metal layer is any one of screen printing, sintering, sputtering, electroplating, pulsed laser deposition, etc., and the metal material of the metal layer is any one of conductive metals such as silver (Ag), copper (Cu), aluminum (Al), palladium (Pd), nickel (Ni) alloy, etc. The specific preparation method of the metal layer, the selection of the metal layer material, and the thickness and shape of the metal layer can be set according to actual needs, and again no specific restrictions are made.

[0090] In a specific implementation example, the method for preparing a high polarization antiferroelectric ceramic capacitor further includes step S8: coating a plastic encapsulation layer on the surface of the high polarization antiferroelectric ceramic capacitor. The plastic encapsulation layer wraps the ceramic dielectric layer, exposing only the metal layer, to prevent the ceramic dielectric layer from being damp or contaminated. The material of the plastic encapsulation layer can be a polymer material such as resin, etc., and can be set according to actual needs, and is not limited here.

[0091] In summary, the present invention proposes a high-polarization antiferroelectric ceramic material, a capacitor and a preparation method thereof. The high-polarization antiferroelectric ceramic material is formed by solid solution of two antiferroelectric materials of different crystal phases in a molar ratio of (1-x):x, wherein x=0.02~0.20, and the high-polarization antiferroelectric ceramic material has a quasi-isomorphic phase boundary structure of a relaxor ferroelectric. The high polarization antiferroelectric ceramic material and the preparation method thereof proposed in the present invention, by precisely controlling the solid solution ratio of different crystalline phase-phase ferroelectric materials, ingeniously introduces the quasi-isomorphic phase boundary structure of the relaxor ferroelectric, not only significantly improves the polarization performance and dielectric performance of the material, but also realizes the overall improvement of its stability performance, opening up a new path for the research and application of antiferroelectric materials; the high polarization antiferroelectric ceramic capacitor and the preparation method thereof proposed in the present invention have extremely high energy storage density due to their unique antiferroelectric properties, under the action of an electric field, antiferroelectric ceramics can undergo a phase transition between an antiferroelectric state and a ferroelectric state, and this process is accompanied by a large amount of energy conversion, so that the capacitor can store and release more energy, the antiferroelectric ceramic capacitor has an excellent power density, can quickly release the stored energy in a short time, and can maintain stable performance in a wide temperature range, which enables them to work reliably under various environmental conditions, and the antiferroelectric ceramic capacitor is expected to play an important role in more fields and promote the progress and development of related science and technology. Therefore, the present invention effectively overcomes certain shortcomings in the prior art and has a high industrial utilization value.

[0092] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A high polarization antiferroelectric ceramic material, characterized in that: The high polarization antiferroelectric ceramic material is formed by solid solution of two antiferroelectric materials of different crystal phases in a molar ratio of (1-x):x, wherein x=0.02-0.20, and the high polarization antiferroelectric ceramic material has a quasi-isomorphic phase boundary structure of a relaxor ferroelectric.

2. The high polarization antiferroelectric ceramic material according to claim 1, characterized in that: The two antiferroelectric materials of different crystal phases are selected from any one of PbZrO3, PbHfO3, AgNbO3 and NaNbO3.

3. The high polarization antiferroelectric ceramic material according to claim 2, characterized in that: The general chemical formula of the high polarization antiferroelectric ceramic material is: (1-x)PbZrO3-xPbHfO3, or (1-x)PbZrO3-xAgNbO3, or (1-x)AgNbO3-xNaNbO3.

4. The high polarization antiferroelectric ceramic material according to claim 1, characterized in that: x=0.025~0.100。 5. A method for preparing a high polarization antiferroelectric ceramic material, characterized in that: The preparation method of the high polarization antiferroelectric ceramic material comprises: S1: weighing oxides and / or carbonates according to a stoichiometric ratio, mixing and then grinding for the first time to obtain a first powder; S2: performing a first heat treatment on the first powder; S3: grinding the first powder for a second time to obtain a second powder; S4: bonding and pressing the second powder to obtain a ceramic material of a preset shape; S5: performing a second heat treatment on the ceramic material to obtain a high-polarization antiferroelectric ceramic material.

6. The method for preparing a high polarization antiferroelectric ceramic material according to claim 5, characterized in that: In step S1: the oxides include lead oxide, zirconium oxide, hafnium oxide and niobium oxide, and the carbonates include silver carbonate and sodium carbonate.

7. The method for preparing a high polarization antiferroelectric ceramic material according to claim 6, characterized in that: In step S1: if a high polarization antiferroelectric ceramic material with a chemical formula of (1-x)PbZrO3-xPbHfO3 is prepared, lead oxide, zirconium oxide and hafnium oxide are weighed; if a high polarization antiferroelectric ceramic material with a chemical formula of (1-x)PbZrO3-xAgNbO3 is prepared, lead oxide, zirconium oxide, silver carbonate and niobium oxide are weighed; if a high polarization antiferroelectric ceramic material with a chemical formula of (1-x)AgNbO3-xNaNbO3 is prepared, silver carbonate, sodium carbonate and niobium oxide are weighed.

8. The method for preparing a high polarization antiferroelectric ceramic material according to claim 5, characterized in that: The first grinding and the second grinding are both performed by ball milling.

9. The method for preparing a high polarization antiferroelectric ceramic material according to claim 5, characterized in that: In step S2: the first heat treatment is a calcination treatment, the calcination treatment temperature ranges from 800°C to 950°C, and the calcination treatment time ranges from 2h to 4h.

10. The method for preparing a high polarization antiferroelectric ceramic material according to claim 5, characterized in that: Before the first heat treatment in step S2, the first powder needs to be pressed.

11. The method for preparing a high polarization antiferroelectric ceramic material according to claim 5, characterized in that: In step S4, the specific steps of bonding and pressing the second powder are as follows: adding a binder to the second powder for granulation to form a flowing powder, taking a proper amount of the flowing powder for tableting and pressing to obtain a ceramic material of a preset shape.

12. The method for preparing a high polarization antiferroelectric ceramic material according to claim 5, characterized in that: In step S5: the second heat treatment is a sintering treatment, the sintering treatment temperature ranges from 1100° C. to 1250° C., and the sintering treatment time ranges from 2 h to 4 h.

13. A high polarization antiferroelectric ceramic capacitor, characterized in that: The high polarization antiferroelectric ceramic capacitor comprises a ceramic dielectric layer and metal layers on the upper and lower surfaces of the ceramic dielectric layer facing each other. The ceramic dielectric layer is the antiferroelectric ceramic material according to any one of claims 1 to 4.

14. A method for preparing a high polarization antiferroelectric ceramic capacitor, characterized in that: The method for preparing the high polarization antiferroelectric ceramic capacitor comprises: the method for preparing the high polarization antiferroelectric ceramic material according to any one of claims 5 to 12 and S6: coating metal on the upper and lower surfaces of the high polarization antiferroelectric ceramic material to form a metal layer; S7: Perform a third heat treatment to form a high polarization antiferroelectric ceramic capacitor.

15. The method for preparing a high polarization antiferroelectric ceramic capacitor according to claim 14, characterized in that: In step S7: the third heat treatment is a sintering treatment, the sintering treatment temperature ranges from 750°C to 850°C, and the sintering treatment time ranges from 15min to 60min.

16. The method for preparing a high polarization antiferroelectric ceramic capacitor according to claim 14, characterized in that: In step S7: the third heat treatment is performed in a nitrogen atmosphere.

Citation Information

Patent Citations

  • Silver niobate-based antiferroelectric ceramic material and preparation method and application thereof

    CN111517787A

  • PbHfO3-based ceramic material and preparation method thereof

    CN112573916A

  • Zirconium tin hafnate lanthanum lead ceramic and preparation method and energy storage application thereof

    CN115872735A

  • Sodium niobate-based lead-free relaxation antiferroelectric energy storage ceramic capacitor and preparation method thereof

    CN116313515A

  • Memory device fabrication through wafer bonding

    US11765908B1